Theoretical approaches to forensic entomology: I. Mathematical model of postfeeding larval dispersal - Von Zuben, C. J. [UNESP]; Bassanezi, R. C.; Dos Reis, S. F.; Godoy, W. A C [UNESP]; Von Zuben, F. J. (Blackwell Wissenschafts Verlag Gmbh, 1996)
An overall theoretical approach to model phenomena of interest for forensic entomology is advanced. Efforts are concentrated in identifying biological attributes at the individual, population and community of the arthropod fauna associated with decomposing human corpses and then incorporating these attributes into mathematical models. In particular in this paper a diffusion model of dispersal of post feeding larvae is described for blowflies, which are the most common insects associated with corpses.